Actin mutations that show suppression with fimbrin mutations identify a likely fimbrin-binding site on actin (The Rockefeller University Press, 1994)
Actin interacts with a large number of different proteins that modulate its assembly and mediate its functions. One such protein is the yeast actin-binding protein Sac6p, which is homologous to vertebrate fimbrin (Adams, A. E. M., D. Botstein, and D. G. Drubin. 1991. Nature (Lond.). 354:404-408.). Sac6p was originally identified both genetically (Adams, A. E. M., and D. Botstein. 1989. Genetics. 121:675-683.) by dominant, reciprocal suppression of a temperature-sensitive yeast actin mutation (act1-1), as well as biochemically (Drubin, D. G., K. G. Miller, and D. Botstein. 1988. J. Cell Biol. 107: 2551-2561.). To identify the region on actin that interacts with Sac6p, we have analyzed eight different act1 mutations that show suppression with sac6 mutant alleles, and have asked whether (a) these mutations occur in a small defined region on the crystal structure of actin; and (b) the mutant actins are defective in their interaction with Sac6p in vitro. Sequence analysis indicates that all of these mutations change residues that cluster in the small domain of the actin crystal structure, suggesting that this region is an important part of the Sac6p-binding domain. Biochemical analysis reveals defects in the ability of several of the mutant actins to bind Sac6p, and a reduction in Sac6p-induced cross-linking of mutant actin filaments. Together, these observations identify a likely site of interaction of fimbrin on actin.